2009
DOI: 10.1073/pnas.0811274106
|View full text |Cite|
|
Sign up to set email alerts
|

Induction of TLR4-target genes entails calcium/calmodulin-dependent regulation of chromatin remodeling

Abstract: Upon toll-like receptor 4 (TLR4) signaling in macrophages, the mammalian Swi/Snf-like BAF chromatin remodeling complex is recruited to many TLR4 target genes where it remodels their chromatin to promote transcription. Here, we show that, surprisingly, recruitment is not sufficient for chromatin remodeling; a second event, dependent on calcium/calmodulin (CaM), is additionally required. Calcium/CaM directly binds the HMG domain of the BAF57 subunit within the BAF complex. Calcium/CaM antagonists, including a Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 52 publications
2
36
0
Order By: Relevance
“…1). SMARCA4 is linked to calcium signaling (Lai et al 2009;Nasipak et al 2015). Literature also supports the idea that SMARCA4 (or the mammalian SWI/SNF complex) regulates lipid metabolism, as it was shown that SMARCA4 regulates PPARG expression, which in turn regulates lipid metabolism in differentiating adipocytes (Salma et al 2004).…”
Section: Discussionmentioning
confidence: 67%
“…1). SMARCA4 is linked to calcium signaling (Lai et al 2009;Nasipak et al 2015). Literature also supports the idea that SMARCA4 (or the mammalian SWI/SNF complex) regulates lipid metabolism, as it was shown that SMARCA4 regulates PPARG expression, which in turn regulates lipid metabolism in differentiating adipocytes (Salma et al 2004).…”
Section: Discussionmentioning
confidence: 67%
“…Thus, to address this kind of question, further technical tools are required to quantitatively compare the nucleosome occupancy between different cell types or under different conditions. BRG1 was recruited to proximal promoter regions, for example, in the interferon signaling pathways (Liu et al 2002;Cui et al 2004) and Toll-like receptor signaling pathways (Lai et al 2009;Ramirez-Carrozzi et al 2009). It was also detected at distal regulatory elements including those of the CIITA gene (Ni et al 2008) and beta-globin gene (O'Neill et al 1999;Im et al 2005), where BRG1 may mediate gene activation by facilitating long-distance chromatin interaction (Kim et al 2009b).…”
Section: Discussionmentioning
confidence: 99%
“…BRG1 is involved in numerous cellular differentiation programs including T cell, erythrocyte, and neuronal lineages (Zhao et al 1998;Bultman et al 2000;Chi et al 2002;Im et al 2005;Wu et al 2007;Jani et al 2008;Wurster and Pazin 2008;Kim et al 2009b). It furthermore regulates gene expression programs in response to interferon stimulation (Liu et al 2002;Cui et al 2004) and Toll-like receptor signaling pathways (Lai et al 2009;Ramirez-Carrozzi et al 2009). In addition to targeting promoter regions, it has been demonstrated that BRG1 is recruited to distal regulatory elements of the CIITA (Ni et al 2008) and HBB (O'Neill et al 1999;Im et al 2005) to mediate their activation by facilitating long-distance chromatin interaction (Kim et al 2009b).…”
mentioning
confidence: 99%
“…Together, these results strongly suggest that Il12b induction requires nucleosome remodeling at the promoter and enhancers by the SWI/SNF-remodeling complexes following their specific recruitment by a recruitment mechanism that remains unknown. Interesting, a study by Chi et al has suggested that, following its recruitment, SWI/SNF activity requires an additional calmodulin-dependent signaling event (Lai et al 2009). …”
Section: Nucleosome Remodeling By Swi/snf Complexesmentioning
confidence: 99%